2023
DOI: 10.1111/apa.16749
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment and the risk of adolescent scoliosis: A large matched cohort study

Abstract: Aim:We aimed to evaluate the risk of developing adolescent scoliosis among recipients of recombinant human growth hormone (rhGH).Methods: This registry-based cohort study included 1314 individuals who initiated rhGH treatment since 2013, treated during 10-18 years of age for at least 6 months. This group was matched to a comparison group of 6570 individuals not treated with rhGH. Demographic and clinical information was extracted from the electronic database. The results are presented using hazard ratios (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…One study showed that rhGH increases the risk of scoliosis in adolescents. 11 A larger sample of data may be needed for support. Current research has shown that the long-term use of rhGH can improve the body composition of 14 Scoliosis should not be considered a reason for refusing rhGH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that rhGH increases the risk of scoliosis in adolescents. 11 A larger sample of data may be needed for support. Current research has shown that the long-term use of rhGH can improve the body composition of 14 Scoliosis should not be considered a reason for refusing rhGH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…rhGH therapy has been considered a possible risk factor for the onset of scoliosis in some studies. 11 However, others have demonstrated that rhGH therapy is not related to the occurrence and development of scoliosis. 7,12,13 This may be related to the population, dose, and age of the patient; however, largesample studies in patients with scoliosis treated with rhGH are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Research highlights the statistical signi cance (P < 0.001) of this heightened fracture risk, encompassing regions such as the skull, neck, and trunk (HR = 1.53), upper limbs (HR = 1.28), and lower extremities (HR = 1.84) [5]. Moreover, studies indicate a correlation between ADHD symptoms and limb fractures in adults [8], with a notable reduction in fracture risk for individuals receiving pharmacological interventions [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these occurrences can be attributed to the unique characteristics of ADHD [78]. Impulsivity, which is a characteristic symptom of ADHD, results in impulsive actions, poor judgment, and a preference for immediate grati cation [10,78]. Research indicates that children with ADHD, despite being capable of recognizing dangers, tend to underestimate the severity of consequences arising from their behaviors [79].…”
Section: Fractures As Causal Factorsmentioning
confidence: 99%
See 1 more Smart Citation